A Win-Win for Deep-Sea Corals and Fishing: Increasing Seafloor Protections While Restoring Fishing Opportunities Off the United States West Coast - Shester, Geoffrey G.; Enticknap, Ben; Mecum, Brianne; Blacow-Draeger, Ashley; Brock, Tara; Murray, Susan (Frontiers in Marine Science, 2021)
On January 1, 2020, the United States (U.S.) government implemented new regulations increasing total closed areas to bottom trawl fishing by 363,513 km2, including a net increase of 44,498 km2 in essential fish habitat conservation areas at fishable depths (<1,280 m) along the West Coast continental shelf and upper slope. At the same time, the government reopened certain bottom trawl fishing grounds originally established to rebuild overfished groundfish. In combination with previously existing conservation areas, the result of these regulations is that bottom trawl fishing is now prohibited in 90% (739,491 km2) of ocean waters in the United States West Coast Exclusive Economic Zone, including 32.6% of shelf (<200 m) depth zones and 56.0% of upper slope depth zones (200-1,280 m), with a disproportionate focus on priority habitat features that are proxies for fish habitat, sensitivity to bottom trawling, and biodiversity. The final spatial management measures include 53 new or modified habitat conservation areas closed to bottom trawling in fishable depths (<1,280 m) and a precautionary prohibition on all bottom contact fishing gears at depths greater than 3,500 m. Together the final set of habitat conservation area closures and openings result in an overall increase in coastwide protections for hard, mixed, and soft substrates; seamounts; submarine canyons; and known and predicted coral, sponge, and pennatulid locations. Finer scale analyses indicate net increases or no change in coral and sponge observations inside protected areas across all regions and depth zones, despite some reductions in total area and hard substrate protected in certain regions. Based on historic bottom trawl effort data, we estimate that the opening of previously closed areas restores 24.6% of fishing effort that was displaced by bottom trawl closures implemented prior to 2020. Here we describe the involvement and approach of the conservation organization, Oceana, to protect seafloor habitats off the United States West Coast, which included a coastwide proposal to modify conservation areas, geospatial analyses, grassroots organizing, media stories, and scientific expeditions using remotely operated vehicles. Our comparison of the new versus previous assemblage of habitat conservation areas demonstrates increased overall habitat protection and fishing opportunities throughout depths and bioregions off the United States West Coast.